Benchmarks for Operative Outcomes of Robotic and Open Radical Prostatectomy: Results from the Health Professionals Follow-up Study - Alemozaffar, Mehrdad; Sanda, Martin; Yecies, Derek; Mucci, Lorelei A.; Stampfer, Meir J.; Kenfield, Stacey A. (European urology, 2015)
Robot-assisted laparoscopic radical prostatectomy (RALP) has become increasingly common; however, there have been no nationwide, population-based, non–claims-based studies to evaluate differences in outcomes between RALP and open radical retropubic prostatectomy (RRP). To determine surgical, oncologic, and health-related quality of life (HRQOL) outcomes following RALP and RRP in a nationwide cohort. We identified 903 men in the Health Professionals Follow-up Study diagnosed with prostate cancer between 2000 and 2010 who underwent radical prostatectomy using RALP (n=282) or RRP (n=621) as primary treatment. Radical prostatectomy. We compared patients undergoing RALP or RRP across a range of perioperative, oncologic, and HRQOL outcomes. Use of RALP increased during the study period, constituting 85.2% of study subjects in 2009, up from 4.5% in 2003. Patients undergoing RALP compared to RRP were less likely to have a lymph node dissection (51.5% vs 85.4%; p<0.0001), had less blood loss (207.4ml vs 852.3ml; p<0.0001), were less likely to receive blood transfusions (4.3% vs 30.3%; p<0.0001), and had shorter hospital stays (1.8 d vs 2.9 d; p<0.0001). Surgical, oncologic, and HRQOL outcomes did not differ significantly among the groups. In multivariate logistic regression models, there were no significant differences in 3- or 5-yr recurrence-free survival comparing RALP versus RRP (hazard ratios: 0.98 [95% confidence interval (CI), 0.46–2.08] and 0.75 [95% CI, 0.18–3.11], respectively). In a nationwide cohort of patients undergoing surgical treatment for prostate cancer, RALP was associated with shorter hospital stay, and lower blood loss and transfusion rates than RRP. Surgical oncologic and HRQOL outcomes were similar between groups. We studied men throughout the United States with prostate cancer who underwent surgical removal of the prostate. We found that robot-assisted laparoscopic radical prostatectomy resulted in shorter hospital stay, less blood loss, and fewer blood transfusions than radical retropubic prostatectomy. There were no differences in cancer control or health-related quality of life. In a nationwide cohort of men with prostate cancer who underwent radical prostatectomy (RP), robot-assisted laparoscopic RP resulted in shorter hospital stay, fewer blood transfusions, and less blood loss than retropubic RP. We observed no differences in cancer progression or health-related quality of life between groups.